2020
DOI: 10.3390/nano10081568
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles as an Alternative to Antibiotics Additive on Extended Boar Semen

Abstract: This study examined the effect of Fe3O4 nanoparticles on boar semen. Beltsville thawing solution without antibiotics was used to extend ejaculates from 5 boars (4 ejaculates/boar). Semen samples of control group (C) and group with Fe3O4 (Fe; 0.192 mg/mL semen) were incubated under routine boar semen storage temperature (17 °C) for 0.5 h and nanoparticles were removed by a magnetic field. Before and after treatment, aliquots of all groups were cultured using standard microbiological methods. The samples after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
1
13
1
2
Order By: Relevance
“…Their activity appeared to be preventive for Staphylococcus spp., Enterococcus spp., and Enterobacteriaceae, and in some samples the microbial reduction was intense; however, the bacterial counts ranged among samples, indicating a non-repetitive result. These findings are not aligned with the reduction of the bacterial load previously described by our research team [ 9 ], regarding the antibacterial action of iron NPs on boar semen. Further investigation is necessary to clarify the factors that suppressed the antimicrobial properties of the NPs in the present study.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…Their activity appeared to be preventive for Staphylococcus spp., Enterococcus spp., and Enterobacteriaceae, and in some samples the microbial reduction was intense; however, the bacterial counts ranged among samples, indicating a non-repetitive result. These findings are not aligned with the reduction of the bacterial load previously described by our research team [ 9 ], regarding the antibacterial action of iron NPs on boar semen. Further investigation is necessary to clarify the factors that suppressed the antimicrobial properties of the NPs in the present study.…”
Section: Discussioncontrasting
confidence: 94%
“…Taking into consideration that in sheep practice AI with fresh cooled semen should be performed within 6–8 h after semen extension [ 25 ], the use of NPs could be justified. In our previous study, no toxic effect was observed for Fe 3 O 4 NPs on boar spermatozoa even after 48 h of storage [ 9 ]. Among the adverse effects of NPs, differences regarding cells’ susceptibility are acknowledged, thus in vitro tests for Nano safety show particular attention to cell type selection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations